RANCANGAN PENYUSUNAN LAPORAN KEUANGAN SESUAI STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK PADA PERUSAHAAN KONTRUKSI DI PT. TUNAS BUMI KARYA - Adella Indah Puspita; Tartila Devy (Jurnal Ekonomi dan Bisnis, 2025)
In today's economic development, the role of accounting is very important to decide something so as not to cause losses, especially in carrying out activities and transactions in a company, for example, such as recording, reporting and interpreting basic economic data in a company. Basically, the accounting process is a service activity whose function is to provide quantitative information, especially those related to finance. This information is expected to be input in the economic and rational decision-making process. In making this report, the company uses financial data so that this report is called a financial report. PT. Tunas Bumi Karya is an entity without public accountability. Even so, the company must still make financial reports in accordance with applicable standards, namely SAK ETAP so that the company can find out how its financial flow and performance are. This study aims to determine how to design and implement financial reports in accordance with the financial accounting standards of entities without public accountability (SAK ETAP) in construction companies at PT. Tunas Bumi Karya. This type of research is descriptive qualitative research. The data in this study are qualitative data with data sources, namely primary data and secondary data. The data collection techniques used are interviews, observation and documentation. The data analysis technique used in this study is to use a descriptive qualitative method using data reduction, data display and drawing conclusions. The results of the study indicate that PT. Tunas Bumi Karya has not implemented financial reporting in accordance with applicable standards, namely SAK ETAP. PT. Tunas Bumi Karya only makes financial reports containing incoming and outgoing money transactions so that they are not in accordance with the standards. Meanwhile, in SAK ETAP, entities must present five types of financial reports, namely Balance Sheet, Profit and Loss Statement, Statement of Changes in Equity, Cash Flow Statement and Notes to the Financial Statements. The obstacle faced by PT. Tunas Bumi Karya in implementing financial reporting in accordance with its standards is the lack of human resources who understand the five types of financial reporting.